Usage of antihistamines and topical corticosteroids in the management of geographic tongue - P Poornachitra; Jayanth K Vadivel (Wolters Kluwer Medknow Publications, 2022)
Geographic tongue (GT) is a benign inflammatory condition of the tongue with map-like areas of erythema. In symptomatic cases, pharmacotherapy is advised to improve quality of life and reduce chances of recurrence. Aim: The study aimed to compare the usage of antihistamines and topical corticosteroids in the management of symptomatic geographic tongue. Objective: The objective was to evaluate the most common drug used in symptomatic geographic tongue management and assess the association between patient gender and drugs given. Materials and Methods: The treatment data of patients (n = 88) was collected from Dental Information Archival System with data from June 2019 to February 2021. The usage of antihistamines and topical steroids was assessed over two weeks to relieve clinical symptoms. Results: The association between drug type, drug name, and reduction in the clinical symptoms after two weeks of the review was statistically significant, with an X2 value of 9.132 at a P value of 0.010 (p < 0.05). The association between drug type, drug name, and gender was not statistically significant (p > 0.05). 38.6% of cases were prescribed Diphenhydramine maleate syrup. It was followed by Betamethasone Mouthwash which was used for 31.8% of cases. Triamcinolone acetonide and Chlorpheniramine tablets were prescribed for 15.9%and 13.6%patients, respectively. Conclusion: Antihistamines should be the first drug type of choice in treating symptomatic GT. Topical steroids could be considered an adjunct or standalone second drug type of choice.